Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To find the inverse function [tex]\( f^{-1}(x) \)[/tex] for the given function [tex]\( f(x) = 16^x \)[/tex], you need to reverse the roles of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] in the equation. Here are the steps to find the inverse function:
1. Rewrite the Function:
Start with the given function [tex]\( f(x) = 16^x \)[/tex]. For the purpose of finding the inverse, let's rewrite it using [tex]\( y \)[/tex]:
[tex]\[ y = 16^x \][/tex]
2. Express [tex]\( x \)[/tex] in Terms of [tex]\( y \)[/tex]:
The goal is to solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]. Start by taking the logarithm of both sides of the equation. In this case, we will take the logarithm to the base 16:
[tex]\[ \log_{16}(y) = \log_{16}(16^x) \][/tex]
Using the logarithmic property [tex]\( \log_b(a^c) = c \cdot \log_b(a) \)[/tex], we get:
[tex]\[ \log_{16}(y) = x \cdot \log_{16}(16) \][/tex]
Since [tex]\( \log_{16}(16) = 1 \)[/tex] (because any number to the power of itself is 1 in logarithms):
[tex]\[ \log_{16}(y) = x \][/tex]
Therefore:
[tex]\[ x = \log_{16}(y) \][/tex]
3. Convert the Logarithmic Base:
To express the answer in a more conventional way, we can convert the base of the logarithm to a natural logarithm (base [tex]\( e \)[/tex]) or common logarithm (base [tex]\( 10 \)[/tex]). One of the properties of logarithms allows us to do so:
[tex]\[ \log_{16}(y) = \frac{\log(y)}{\log(16)} \][/tex]
or using the natural logarithm:
[tex]\[ \log_{16}(y) = \frac{\ln(y)}{\ln(16)} \][/tex]
4. Write the Inverse Function:
Now, express [tex]\( f^{-1}(x) \)[/tex]:
[tex]\[ f^{-1}(x) = \frac{\log(x)}{\log(16)} \][/tex]
or using the natural logarithm:
[tex]\[ f^{-1}(x) = \frac{\ln(x)}{\ln(16)} \][/tex]
Thus, the inverse function of [tex]\( f(x) = 16^x \)[/tex] is:
[tex]\[ f^{-1}(x) = \frac{\log(x)}{\log(16)} \][/tex]
1. Rewrite the Function:
Start with the given function [tex]\( f(x) = 16^x \)[/tex]. For the purpose of finding the inverse, let's rewrite it using [tex]\( y \)[/tex]:
[tex]\[ y = 16^x \][/tex]
2. Express [tex]\( x \)[/tex] in Terms of [tex]\( y \)[/tex]:
The goal is to solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]. Start by taking the logarithm of both sides of the equation. In this case, we will take the logarithm to the base 16:
[tex]\[ \log_{16}(y) = \log_{16}(16^x) \][/tex]
Using the logarithmic property [tex]\( \log_b(a^c) = c \cdot \log_b(a) \)[/tex], we get:
[tex]\[ \log_{16}(y) = x \cdot \log_{16}(16) \][/tex]
Since [tex]\( \log_{16}(16) = 1 \)[/tex] (because any number to the power of itself is 1 in logarithms):
[tex]\[ \log_{16}(y) = x \][/tex]
Therefore:
[tex]\[ x = \log_{16}(y) \][/tex]
3. Convert the Logarithmic Base:
To express the answer in a more conventional way, we can convert the base of the logarithm to a natural logarithm (base [tex]\( e \)[/tex]) or common logarithm (base [tex]\( 10 \)[/tex]). One of the properties of logarithms allows us to do so:
[tex]\[ \log_{16}(y) = \frac{\log(y)}{\log(16)} \][/tex]
or using the natural logarithm:
[tex]\[ \log_{16}(y) = \frac{\ln(y)}{\ln(16)} \][/tex]
4. Write the Inverse Function:
Now, express [tex]\( f^{-1}(x) \)[/tex]:
[tex]\[ f^{-1}(x) = \frac{\log(x)}{\log(16)} \][/tex]
or using the natural logarithm:
[tex]\[ f^{-1}(x) = \frac{\ln(x)}{\ln(16)} \][/tex]
Thus, the inverse function of [tex]\( f(x) = 16^x \)[/tex] is:
[tex]\[ f^{-1}(x) = \frac{\log(x)}{\log(16)} \][/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.